Preparation and Extensive Characterization of Fullerenol C60 - Abdulkareem M. A. Al-Sammarraie (Journal of Global Pharma Technology, 2016)
Recently, functionalization processes onto the outer surface of fullerenes such as C60 and C70 with various groups attracted large interesting from scientists, which including convert sp2 hybridization carbon atoms to sp3 hybridization that aim for enhancing its solubility in an organic polar solvent. This work converts the fullerene C60 successfully to hydroxyl functionalized fullerene which called fullerenol C60.The hydroxyl functionalized fullerene C60 nano-product was characterized using FTIR, 1H-NMR, 13C-NMR, AFM, SEM, TEM, EDX, TGA, and XRD examinations, they proved the fullerenol C60 structure and demonstrated the remarkable change in fullerene C60 topography from un-uniform particles to shape like spherical with high aggregation.Keywords: Fullerene C60, fullerenol, functionalization.